O Bioma Pampa como estratégia contextualizadora na formação de professores para o ensino de ciências nos anos iniciais - Pinto , Luiza Frigo (2025)
Teaching Science in the Early Years of Elementary Education contributes to the acquisition of basic concepts of Natural Sciences, the understanding of scientific content, and awakens in students an interest, curiosity, and a sense of investigation, which will contribute to their intellectual development. In this sense, environmental themes can permeate the discussion, aiding in the construction of new knowledge and the recognition of the importance of awareness and preservation of local ecosystems. Thus, it is noteworthy that the Pampa biome, as a unique and biodiverse ecosystem that spans southern Brazil, Uruguay, and Argentina, has singular ecological relevance and is underrepresented and undervalued in the educational context. The present study analyzed the potential contributions of the Pampa biome as a contextualizing strategy for teaching Science, based on an investigation with Early Years teachers in the municipality of Jaguari/RS. The methodology is characterized as qualitative, of the pedagogical intervention type, and regarding its objectives, it is descriptive and exploratory research, structured around the Problematization Methodology through the five stages of Maguerez’s Arc. Therefore, in the Observation of reality, a study of official documents was carried out, a questionnaire was constructed for application to teachers, and Article I was developed. The results indicated that the Pampa biome is rarely addressed in relation to teaching and demonstrated the possibility of linking the theme to Environmental Education. In the Key points, topics were established based on the Observation of reality, including Pampa Biome, Science Teaching, Early Years, Teacher Training, Contextualization, Interdisciplinarity and Scientific Literacy. In the Theorization, a deeper exploration of the points outlined in the previous stage was conducted, forming the topics for the literature review. In the Hypotheses of Solution, the questionnaires were applied, results were analyzed, and two manuscripts were drafted. In Manuscript I, the results indicate that teachers recognize the importance of Science teaching and the need to provide more engaging and attractive classes, constructing their plans based on textbooks and the Common National Curriculum Base (BNCC). Manuscript II results demonstrated, according to the teachers investigated, that students have a limited understanding of biomes. However, they show knowledge of the Pampa, even though this theme has not been addressed in the school curriculum. It also highlights a teaching approach focused on conservation and environmental awareness. In this stage of the Arc, a formative process was also developed to be carried out with Early Years teachers. Finally, in the Application to Reality, the formative process was implemented, resulting in Manuscript III, where the results revealed the necessity of addressing Science teaching in the Early Years, the teachers' receptiveness to the theme, and the importance of contextualization to make learning more meaningful. It is understood that the difficulties faced in addressing the Pampa biome in the Early Years may stem from the teachers' initial training, which prioritizes pedagogical aspects, textbooks with summarized information on the theme, and lack of attention to guidelines in official documents about the importance of developing content related to students' reality. From the formative process, it was observed that the Pampa biome can be established as a contextualizing strategy for teaching Science in the Early Years, as it encompasses a variety of subjects that can be explored throughout the school year and contributes to cultivating a sense of belonging among students regarding their local environment. Additionally, as teachers reflect on their practice, they can re-signify, adopting a contextualization perspective in their lesson planning. Finally, studies of such relevance have the potential to improve the quality of teaching offered in the Early Years, considering that from an early age, students will be engaged in meaningful, reflective practices oriented towards scientific knowledge.